2020
DOI: 10.12890/2020_001905
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retention and Severe Hyponatremia: An Unusual Presentation of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) was first reported in Wuhan, China, in December 2019. The disease is caused by severe acute respiratory syndrome virus coronavirus 2 (SARS-CoV-2). A few published cases have linked COVID-19 and hyponatremia. The mechanism of hyponatremia in these cases is related to the syndrome of inappropriate antidiuretic hormone secretion (SIADH). Here we present a unique case of urinary retention and SIADH as unusual presenting features of SARS-CoV-2 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Moreover, the prospective evaluation of 90,889 hospitalized adult patients demonstrated that mixed dysnatremia, hospital-acquired hypernatremia, persistent hypernatremia and 'hyponatremia overcorrected to hypernatremia' were independent indicators of in-hospital mortality ( 23 ). In the last case, the life-threatening occurrence of osmotic demyelination should not be forgotten and has been documented also in a case of overcorrected COVID-19-related SIAD ( 37 ).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the prospective evaluation of 90,889 hospitalized adult patients demonstrated that mixed dysnatremia, hospital-acquired hypernatremia, persistent hypernatremia and 'hyponatremia overcorrected to hypernatremia' were independent indicators of in-hospital mortality ( 23 ). In the last case, the life-threatening occurrence of osmotic demyelination should not be forgotten and has been documented also in a case of overcorrected COVID-19-related SIAD ( 37 ).…”
Section: Discussionmentioning
confidence: 94%
“…The syndrome of inappropriate antidiuretic hormone (SIADH) has been associated with SARS-CoV-2 acute infection in adults, but the etiology is unknown. 4,5 Hypercytokinemia activating the nonosmotic secretion of ADH and damage to the lung tissue stimulating ADH secretion via hypoxic pulmonary hypoconstriction have been postulated. 4 To our knowledge, SIADH has not been previously described as a complication of MIS-C.…”
mentioning
confidence: 99%